Role of Second-Generation Drug-Eluting Stents and Bypass Grafting in Coronary Artery Disease: A Systematic Review and Meta-analysis - Linjuan Guo; Ying Ding; Fuwei Liu; Wengen Zhu; Xinghua Jiang (Cardiovascular Innovations and Applications, 2017)
Background: The safety and efficacy of coronary artery bypass grafting (CABG) and second-generation drug-eluting stents (DESs) in patients with coronary artery disease (CAD) remain controversial. Therefore we aimed to compare the outcomes of CAD patients treated with CABG and second-generation DESs. Methods: We systematically searched the PubMed, Cochrane Library, Ovid, and Elsevier databases. Studies comparing second-generation DESs with CABG in CAD patients were included. RevMan 5.3 was used to extract and pool the data from the applicable studies. Results: Six trials (N=6604 participants) were included in this meta-analysis. Among all of the CAD patients, second-generation DESs were associated with no differences in the risks of all-cause death [risk ratio (RR) 1.18, 95% confidence interval (CI) 0.98–1.43, P=0.09], cardiovascular death (RR 1.14, 95% CI 0.81–1.59, P=0.45), myocardial infarction (RR 1.22, 95% CI 0.98–1.54, P=0.08), and stroke (RR 0.83, 95% CI 0.59–1.17, P=0.29), but increased the risks of revascularization (RR 1.95, 95% CI 1.66–2.30, P<0.001) and major adverse cardiac and cerebrovascular events (RR 1.72, 95% CI:1.31–2.26, P<0.001) when compared with CABG. Conclusions: In the treatment of CAD patients, second-generation DESs was not associated with increased risks of all-cause death, cardiovascular death, myocardial infarction, and stroke, but increased the risks of revascularization and major adverse cardiac and cerebrovascular events when compared with CABG.